Characterizations of protein S-nitrosylation and the 26S proteasome network in the malaria parasite Plasmodium falciparum - Wang, Lihui; Justus Liebig University Giessen (My University, 2014)
Malaria remains a detrimental tropical disease caused by the protozoan parasites known as Plasmodium and is threatening almost half the worlds population. Nitric oxide (NO) and NO-derived reactive nitrogen species are well-known in vivo effector molecules for controlling the malaria parasites in both mosquito transmitting vectors and humans. However, NO targets and the profound mechanism of NO actions in the malaria parasites remain largely unexplored. Protein S-nitrosylation (SNO), a protein posttranslational modification induced by NO and RNS, has been recognized to substantially mediate diverse biological effects of NO in vivo. In this thesis, we describe a comprehensive analysis of protein S-nitrosylation in the most deadly malaria parasite Plasmodium falciparum. By using a biotin-switch assay coupled with mass spectrometry, we have identified, for the first time, 319 potential S-nitrosylation targets in Plasmodium falciparum that are widespread in various cellular pathways. Interestingly, some metabolic pathways such as glycolysis show an accumulation of S-nitrosylated proteins, indicating a high susceptibility to NO-mediated regulation. A major redox protein, P. falciparum thioredoxin 1 (PfTrx1) was found to be able to transfer or remove NO to or from other proteins, thus possibly mediating the transnitrosylation and denitrosylation in the parasites. We thus propose a redox status-based model of the role of PfTrx1 in the regulation of SNO in P. falciparum. The model suggests that PfTrx1 may protect the parasite from nitrosative stress via protein denitrosylation, whereas upon intensive nitrosative stress PfTrx1 may switch its role to transduce nitrosative stress via protein transnitrosylation. We believe that this study contributes to our understanding of how central metabolic processes in malaria parasites are regulated by NO and suggests that P. falciparum employs the thioredoxin system to deal with the nitrosative challenge.The protein turnover via the ubiquitin-proteasome system (UPS) is well-acknowledged as an essential mechanism profoundly involved in many cellular events in eukaryotes. The classical UPS pathway in eukaryotes typically consists of polyubiquitination of protein substrates, polyubiquitinylated substrates transportation, and substrate recognition by the eukaryotic 26S proteasome, and substrate degradation by the proteasome. Although compelling data have indicated the presence of a functional 26S proteasome network in P. falciparum, the componential integrity and the functionality of the plasmodial 26S proteasome has not been systematically studied so far. In this thesis, we aimed to characterize the mechanism of substrate recognition by the 26S proteasome of P. falciparum. By using in silico analysis and biochemical investigations, we have identified three ubiquitin receptor domains inherited by two plasmodial proteasome subunits, the Rpn10 and Rpn13 subunits. These newly identified plasmodial ubiquitin receptor domains include two putative ubiquitin-interacting motif (UIM) domains and a putative Pleckstrin-like receptor for ubiquitin (Pru) domain. The P. falciparum UIM domains (PfUIMs) and Pru domain (PfPru) were demonstrated to bind ubiquitin-like domains (UBLs) from the plasmodial homologues of Rad23 and Dsk2, which are important UBL-containing proteins involved in the transportation of proteasomal substrates to the 26S proteasome. Strikingly, only PfUIM2 domain was found to be able to directly bind polyubiquitin chains, indicating that PfUIM2 is the site for the direct recognition of polyubiquitinylated substrates for proteasomal degradation. Based on the affinity of PfUIM2 domain to the UBL domain of the plasmodial Rad23, we successfully established a simple and efficient affinity purification method to isolate the P. falciparum 26S proteasome complex together with a number of putative proteasome-interacting proteins (PIPs) directly from the parasite extracts. With this method, we provide the first insight into the componential composition of the plasmodial 26S proteasome. More importantly, the co-purification of putative PIPs in P. falciparum has allowed us to take a first view of the protein metabolism network orchestrated by the plasmodial UPS, and may provide new targets for developing novel antimalarial agents targeting the plasmodial UPS or related pathways.

Die verheerende tropische Erkrankung Malaria wird durch Protozoen, bekannt als Plasmodien, hervorgerufen und bedroht fast die Hälfte der Weltbevölkerung. Stickstoffmonoxid (NO) und die von ihm abgeleiteten reaktiven Stickstoffspezies (RNS) sind bekannte in vivo Effektormoleküle, welche den Malariaparasiten sowohl im transmittierenden Vektor als auch im Menschen kontrollieren. Jedoch gilt der profunde Mechanismus des NO-Einflusses und seine Zielmoleküle im Malariaerreger als weitgehend unerforscht. Die S-Nitrosylierung von Proteinen (SNO), eine posttranslationale Modifikation induziert durch NO und RNS, stellt einen substantiellen Mediator diverser biologischer Effekte von NO in vivo dar. Mit dieser Arbeit stellen wir eine umfassende Analyse der S-Nitrosylierung von Proteinen in dem tödlichsten der Malariaparasiten, Plasmodium falciparum, dar. Durch die Anwendung des Biotin Switch Assays gekoppelt mit Massenspektrometrie gelang es uns zum ersten Mal 319 potentielle Ziele der S-Nitrosylierung in Plasmodium falciparum darzustellen, die in einer Vielzahl von zellulären Abläufen zu finden sind. Interessanterweise zeigen einige Stoffwechselwege, wie die Glykolyse, eine Akkumulation von S-nitrosylierten Proteinen, welches eine hohe Empfänglichkeit für NO-vermittelte Regulationen vermuten lässt. Das wichtige Redoxprotein Thioredoxin 1 aus P. falciparum (PfTrx1) konnte als möglicher Vermittler von Transnitrosylierung oder Denitrosylierung im Parasiten identifiziert werden, indem es in der Lage ist, NO zu anderen Proteinen zu transportieren oder diese von ihnen zu entfernen. Wir vermuten folglich ein Redoxstatus-basiertes Modell der Rolle von PfTrx1 in der Regulation von SNO in P. falciparum. Das Modell weist darauf hin, dass PfTrx1 den Parasiten vor Stickstoffstress durch Denitrosylierung von Proteinen schützen kann, wohingegen PfTrx1 bei hohem NO bedingtem Stress seine Funktion zur Transnitrosylierung von Proteinen ändert. Wir sind der Meinung, dass diese Arbeit zum Verständnis beiträgt, wie zentrale metabolische Prozesse im Malariaparasiten durch NO reguliert werden können und vermuten, dass P. falciparum das Thioredoxsystem nutzt, um Stickstoffstress entgegenzuwirken. Der Proteinumsatz durch das Ubiquitin-Proteasom-System (UPS) ist als essentieller Mechanismus, der tiefgreifend in viele zelluläre Ereignisse in Eukaryoten eingreift, bekannt. Der klassische UPS-Weg in Eukaryoten besteht typischerweise aus einer Polyubiquitinylierung von Proteinsubstraten, deren Transport und Substraterkennung durch das eukaryotische 26S Proteasom sowie der Degradation dieser Substrate durch das Proteasom. Obwohl eindeutige Daten die Präsenz eines funktionellen 26S-Proteasom-Netzwerkes in P. falciparum vermuten lassen, wurde die Integrität und Funktionalität des plasmodialen 26S Proteasoms bisher nicht systematisch erforscht. Mit der vorliegenden Arbeit adressieren wir eine Charakterisierung des Mechanismus der Substraterkennung des 26S Proteasoms von P. falciparum. Durch die Verwendung von in silico Analysen und biochemischen Untersuchungen konnten wir drei Ubiquitin-Rezeptoreinheiten auf zwei plasmodialen Proteasom-Untereinheiten, Rpn10 und Rpn13, bestimmen. Diese neu identifizierten plasmodialen Ubiquitin-Rezeptoreinheiten beinhalten zwei potentielle Ubiquitin-Interaktionsmotive (UIM) und eine potentielle Pleckstrin-like Rezeptordomäne für Ubiquitin (Pru). Die P. falciparum UIM-Domänen (PfUIMs) und Pru-Domäne (PfPru) können an Ubiquitin-like-Domänen (UBLs) der plasmodialen Homologe von Rad23 und Dsk2 binden, welche wichtige UBL-beinhaltende Proteine darstellen, die im Transport zum 26S Proteasom involviert sind. Erstaunlicherweise war nur PfUIM2 in der Lage direkt Ubiquitinketten zu binden, was darauf hinweist, dass PfUIM2 zur direkten Erkennung von polyubiquitinylierten Substraten zur proteasomalen Degradation dient. Basierend auf der Affinität der PfUIM2-Domäne zur UBL-Domäne der plasmodialen Rad23, konnten wir eine einfache und effektive Methode der Affinitätsreinigung zur direkten Isolierung des P. falciparum 26S Proteasomskomplexes zusammen mit einer Reihe potentieller Proteasom-interagierender Proteine (PIPs) aus dem Parasitenextrakt entwickeln. Mit dieser Methode konnten wir erste Einblicke in die Zusammenstellung der Komponenten des plasmodialen 26S Proteasoms liefern. Zudem erlaubte uns die Co-Reinigung der potentiellen PIPs aus P. falciparum einen ersten Blick auf das metabolische Proteinnetzwerk instrumentalisiert durch das plasmodiale UPS und bietet neue Ziele zur Entwicklung neuartiger Antimalariawirkstoffe, welche auf die plasmodiale UPS oder verwandte Stoffwechselwege abzielt.
Charakterisierungen der Protein-S-Nitrosylierung und des 26S-Proteasom-Netzwerkes im Malaria-Parasiten Plasmodium falciparum
Keywords: Malaria; Plasmodium falciparum; Nitric oxide; Protein S-nitrosylation; Proteasome; ddc:540